Global analysis of peroxy radicals and peroxy radical-water complexation using the STOCHEM-CRI global chemistry and transport model. (April 2015) - Khan, M.A.H.; Cooke, M.C.; Utembe, S.R.; Archibald, A.T.; Derwent, R.G.; Jenkin, M.E.; Morris, W.C.; South, N.; Hansen, J.C.; Francisco, J.S.; Percival, C.J.; Shallcross, D.E.
Abstract: The importance of peroxy radical (RO2 ) chemistry in the troposphere is investigated using the STOCHEM-CRI global chemistry and transport model. The oxidation of VOCs leads to the formation of RO2 radicals which are dominated by CH3 O2 (83%), RCO3 (5%), isoprene derived peroxy radicals (6%), and terpene derived peroxy radicals (1%). A good correlation between model and field measurements for total RO2 for most of the selected stations suggests that they are appropriate background sites as the atmospheric processes occurring at these stations are representative of the chemistry taking place within the entire model grid square in which they are located. The seasonality exhibited by RO2 has been studied, with well-defined cycles (highest in summer and lowest in winter) seen in both hemispheres. Peroxy radical-water complexes, whilst not represented using Chemical Transport Models (CTMs) previously, are postulated to perturb RO2 chemistry. The significance of water clusters (RO2 .H2 O) is investigated using the STOCHEM-CRI model and reveals that at 300 K the proportion of RO2 participating in complexation with water is approximately 12% in the tropics. Isoprene derived radicals are the most strongly bound of RO2 species investigated and their degree of complexation at approx. 300 K far surpasses that of the generic peroxy radicals by 3–5%. At higher altitudes (approx. 8 km) characterized by sub-ambient temperatures, the fraction of RO2 .H2 O complex that can exist is approximately 17% in the upper troposphere above Mace Head (Northern Hemisphere), 14% above Cape Grim (Southern Hemisphere), and 8% above Mauna Loa (Tropics). Highlights: RO2 .H2 O complexes are postulated to perturb RO2 chemistry. The presence of RO2 .H2 O complexes has been found substantially in tropics. RO2 .H2 O complexation appears to play a significant role in the upper troposphere.